2022
DOI: 10.1186/s12974-022-02497-9
|View full text |Cite
|
Sign up to set email alerts
|

The primary macrophage chemokine, CCL2, is not necessary after a peripheral nerve injury for macrophage recruitment and activation or for conditioning lesion enhanced peripheral regeneration

Abstract: Background Peripheral nerve injuries stimulate the regenerative capacity of injured neurons through a neuroimmune phenomenon termed the conditioning lesion (CL) response. This response depends on macrophage accumulation in affected dorsal root ganglia (DRGs) and peripheral nerves. The macrophage chemokine CCL2 is upregulated after injury and is allegedly required for stimulating macrophage recruitment and pro-regenerative signaling through its receptor, CCR2. In these tissues, CCL2 is putativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Although we cannot rule out the possibility that motoneuron- and microglia-derived CCL2 compensate for each other, the results agree with a recent communication reaching similar conclusions in DRGs and peripheral nerves after similar injuries. 24 The main difference we observed in mice with ccl2 removed from microglia was less variation in average number of cells per section. Coefficient of variations were relatively low for MG Δ ccl2 mice (19.6%) and larger for MN Δ ccl2 (47.5%) and ccl2 flx/flx (73.0%) mice.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Although we cannot rule out the possibility that motoneuron- and microglia-derived CCL2 compensate for each other, the results agree with a recent communication reaching similar conclusions in DRGs and peripheral nerves after similar injuries. 24 The main difference we observed in mice with ccl2 removed from microglia was less variation in average number of cells per section. Coefficient of variations were relatively low for MG Δ ccl2 mice (19.6%) and larger for MN Δ ccl2 (47.5%) and ccl2 flx/flx (73.0%) mice.…”
Section: Resultsmentioning
confidence: 70%
“…However, an alternative view of CCL2 being dispensable for CCR2 + cell recruitment was recently proposed. 24 …”
Section: Resultsmentioning
confidence: 99%
“…However, upregulation of two specific genes retained our attention as possible markers for a new inflammatory response shift. First, upregulation of the macrophage Ccl12 gene (orthologous to Ccl2) encoding a chemoattractant cytokine very common in the recruitment of immune cells [126][127][128] . Second, upregulation of the specific SGC Gfap gene, suggesting that SGCs have entered into a reactivity state 24,[83][84][85]119 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, loss of either CCR2 or CCL2 was reported to dramatically impair DN and DRG macrophage accumulation [ 18 , 19 , 33 , 34 ] and CL-enhanced regeneration in vitro [ 18 , 33 ], suggesting MDMs and DRG macrophages are necessary for the CL response. However, recent studies demonstrated that the DRG macrophage response is dominated by proliferation of a true resident population [ 16 , 17 ] independent of CCR2 signaling [ 35 ]. The nerve response is dominated by MDMs and thus is impaired in Ccr2 null animals [ 17 , 19 , 36 ], although resident compensation results in only a 50% macrophage reduction [ 35 ].…”
Section: Introductionmentioning
confidence: 99%